Estudo da variação temporal da presença de estrógenos em duas ETE do Estado de São Paulo - Pimentel, Paulo Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In recent years emerging contaminants in sewage at concentrations of the order of ng L-1 or μg L-1 has aroused interest in the scientific community by presenting potential to cause adverse effects in humans and animals. Among the emerging contaminants in sewage, we can mention the natural estrogens (17 β-estradiol, estrone, estriol) and synthetic (17 α-ethinylestradiol) which have been of concern because of the large amount released daily into the environment sewage treated or not. Due to the limited studies on the efficiency of Brazilian wastewater treatment plants in the removal of natural and synthetic estrogens, motivated this research in two cities in the state of São Paulo, which will be called the city A and city B, both belonging to UGRHI 9 Mogi-Guaçu and UGRHI 13 Tietê-Jacaré. In the ETE city B raw sewage is treated Cyclic Activated Sludge System, batch; and the ETE city A, raw sewage is treated through a mixed system, using the technology of Upflow Anaerobic Digester and complemented with a treatment by facultative lagoons. The determination of estrogens was performed by optimized and validated method including SPE (C18) for the extraction and pre-concentration of analytes in samples of raw sewage and treated (250 mL) and analysis by HPLC/FLU. The accuracy showed average values over 71% for E2, 78% for EE2, and 80% for E1 with less than or equal to 15% precision for spiked samples. The limits of quantification were 32 ng L-1 for E2; 100 ng L-1 for EE2; and 3,2 μg L-1 for E1, for all matrices investigated. The environmental study includes sampling of raw sewage and treated the WWTP city A and city B for nine months. The concentrations found in raw sewage ranged from 312-2966 ng L-1 for E2; 116-1309 ng L-1 for EE2; and 16-168 μg L-1 for E1; whereas the treated sewage for the concentrations ranged from 95-1591 ng L-1 for E2; 155-4540 ng L-1 for EE2 and 5-80 μg L-1 for E1. In this study the average efficiency observed in...

Nos últimos anos os contaminantes emergentes presentes nos esgotos sanitários em concentrações da ordem de ng L-1 ou μg L-1 tem despertado interesse na comunidade cientifica por apresentar potencial para exercer efeitos adversos em humanos e animais. Dentre os contaminantes emergentes presentes nos esgotos sanitários, podemos citar os estrógenos naturais (17β-estradiol, estrona, estriol) e sintético (17α-etinilestradiol) os quais têm sido motivo de preocupação devido a grande quantidade lançada diariamente no ambiente, via esgotos sanitários tratados ou não. Devido à existência de poucos estudos publicados na literatura sobre a eficiência das estações de tratamentos de efluentes brasileiras na remoção dos estrógenos naturais e sintéticos, motivou a realização desta pesquisa em duas cidades do estado de São Paulo, que serão chamadas de cidade A e cidade B, ambas pertencentes às UGRHI 9 Mogi-Guaçu e a UGRHI 13 Tietê-Jacaré. Na ETE – cidade B o esgoto bruto é tratado através do Sistema Cíclico de Lodos Ativados, por batelada; e na ETE cidade A, o esgoto bruto é tratado através de um sistema misto, utilizando a tecnologia de Digestor Anaeróbio de Fluxo Ascendente e complementado com um pós-tratamento através de lagoas facultativas. A determinação dos estrógenos foi efetuada por método otimizado e validado que inclui SPE (C18) para extração e pré-concentração dos analitos em amostras de esgoto sanitário bruto e tratado (250 mL) e analise por HPLC/FLU. A exatidão apresentou valores médios acima de 71% para 17  estradiol (E2); 78% para 17  etinilestradiol (EE2); e 80% para estrona (E1), com precisão menor ou igual a 15% para as amostras fortificadas. Os limites de quantificação foram 32 ng L-1 para E2; 100 ng L-1 para EE2; e 3,2 μg L-1 para E1, para ambas as matrizes estudadas. O estudo ambiental incluiu a amostragem do esgoto sanitário bruto e tratado das ETE cidade A e cidade B, durante...
Keywords: Química ambiental; Esgotos; Estrogênios; Contaminantes emergentes na água